Cutting Edge: A Comprehensive Guide to Colorectal Cancer Surgery in Inflammatory Bowel Diseases - Ionut Eduard Iordache; Lucian-Flavius Herlo; Razvan Popescu; Daniel Ovidiu Costea; Luana Alexandrescu; Adrian Paul Suceveanu; Sorin Deacu; Gabriela Isabela Baltatescu; Alina Doina Nicoara; Nicoleta Leopa; Andreea Nelson Twakor; Andrei Octavian Iordache; et al. (Journal of Mind and Medical Sciences)
Over the past two decades, surgical techniques in colorectal cancer (CRC) have improved patient outcomes through precision and reduced invasiveness. Open colectomy, laparoscopic surgery, robotic-assisted procedures, and advanced rectal cancer treatments such as total mesorectal excision (TME) and transanal TME are discussed in this article. Traditional open colectomy offers reliable resection but takes longer to recover. Laparoscopic surgery transformed CRC care by improving oncological outcomes, postoperative pain, and recovery. Automated surgery improves laparoscopy’s dexterity, precision, and 3D visualisation, making it ideal for rectal cancer pelvic dissections. TME is the gold standard treatment for rectal cancer, minimising local recurrence, while TaTME improves access for low-lying tumours, preserving the sphincter. In metastatic CRC, palliative procedures help manage blockage, perforation, and bleeding. Clinical examples and landmark trials show each technique’s efficacy in personalised care. Advanced surgical techniques and multidisciplinary approaches have improved CRC survival and quality of life. Advances in CRC treatment require creativity and customised surgery.